"Maybe we can work together": researchers' outcome expectations for sharing knowledge on social media. Issue 4 (26th October 2020) - Alshahrani, Hussain; Pennington, Diane
Abstract : Purpose: This study aims to investigate the outcomes that researchers expect from using social media for knowledge sharing and to explore how these outcomes impact their use. Design/methodology/approach: The authors conducted 30 semi-structured interviews with researchers at a major Scottish university. They analysed the interview transcripts using directed content analysis. Findings: Researchers expect social and personal outcomes from the use of social media to share knowledge. Each type has positive and negative forms. The positive outcomes motivate researchers to use it, whereas negative outcomes prevent them from using it. Research limitations/implications: This study extends the integrative theoretical framework of outcome expectations within the social cognitive theory by exploring these outcomes and their relative amount of influence on sharing ideas, experiences, questions and research outputs on social media. While the participants included academic staff and postdoctoral researchers, the majority were PhD students. Practical implications: The findings will help individual researchers and universities to use social media effectively in sharing ideas and promoting research through identifying the positive outcomes. Identifying the negative outcomes will help in using solutions to overcome them. Originality/value: This is the first known study to investigate the outcome expectations that impact researchers' use of social media for knowledge sharing.